2014
DOI: 10.1371/journal.pone.0107357
|View full text |Cite
|
Sign up to set email alerts
|

Does Rearing Laying Hens in Aviaries Adversely Affect Long-Term Welfare following Transfer to Furnished Cages?

Abstract: This study tests the hypothesis that hens that are reared in aviaries but produce in furnished cages experience poorer welfare in production than hens reared in caged systems. This hypothesis is based on the suggestion that the spatial restriction associated with the transfer from aviaries to cages results in frustration or stress for the aviary reared birds. To assess the difference in welfare between aviary and cage reared hens in production, non-beak trimmed white leghorn birds from both rearing backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The study by Tahamtani et al ( 25 ), using birds that were identical to those used in the current study, indicated that aviary-rearing resulted in birds that displayed more comfort behavior at 19 weeks of age but had higher mortality throughout the production period. Higher expression of comfort behavior in aviary-reared birds suggests that they had better welfare, whereas the greater mortality throughout production suggests the opposite.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The study by Tahamtani et al ( 25 ), using birds that were identical to those used in the current study, indicated that aviary-rearing resulted in birds that displayed more comfort behavior at 19 weeks of age but had higher mortality throughout the production period. Higher expression of comfort behavior in aviary-reared birds suggests that they had better welfare, whereas the greater mortality throughout production suggests the opposite.…”
Section: Discussionsupporting
confidence: 53%
“…The current study focused on the early production phase soon after transfer to the production facility. Future research could test whether the effect of rearing persists to later stages of development, especially given the previously reported negative effects of aviary rearing on mortality throughout the production phase ( 25 ). Farmers are unlikely to use aviary rearing as a method of reducing fearfulness in laying hens specifically, especially if they should later be used for producing in cages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The general activity of floor-reared pullets following transfer to cages is reduced in the first days after transfer relative to cage-reared birds, likely reflecting the greater change that the floor-reared birds were thus exposed to (Craig et al., 1988 ). Another commercial scale study showed that aviary-reared birds exhibited more alert behavior near to a novel object than did cage-reared birds at 3, but not at 5, weeks after transfer (Tahamtani et al., 2014 ). Alert behavior in response to a novel object in the home environment is associated with a positive choice and therefore is an indicator of good welfare in laying hens (Nicol et al., 2009 ; Nicol et al., 2011 ).…”
Section: Rearing Conditions Affecting the Welfare Of Laying Hensmentioning
confidence: 99%